2008
DOI: 10.1021/jp7102897
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Aminolysis of Anhydrides: Effect of the Catalysis to the Reaction of Succinic Anhydride with Methylamine in Gas Phase and Nonpolar Solution

Abstract: Different possible pathways of the aminolysis reaction of succinic anhydride were investigated by applying high level electronic structure theory, examining the general base catalysis by amine and the general acid catalysis by acetic acid, and studying the effect of solvent. The density functional theory at the B3LYP/6-31G(d) and B3LYP/6-311++G(d,p) levels was employed to investigate the reaction pathways for the aminolysis reaction between succinic anhydride and methylamine. The single point ab initio calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…22,23 A second amine molecule can also facilitate the proton transfer via the general base pathway. 2427 Theoretical 19 and experimental 28 studies have shown that 2-pyridinone, acetic acid, 29 and triazabicyclodecene (TBD) 30 can also act as proton conduits. In many systems, the two-step and concerted pathways are nearly isoelectronic; greater differentiation comes from steric and electronic interactions between the reacting partners.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 A second amine molecule can also facilitate the proton transfer via the general base pathway. 2427 Theoretical 19 and experimental 28 studies have shown that 2-pyridinone, acetic acid, 29 and triazabicyclodecene (TBD) 30 can also act as proton conduits. In many systems, the two-step and concerted pathways are nearly isoelectronic; greater differentiation comes from steric and electronic interactions between the reacting partners.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that most computational studies reported so far only support the concerted and the neutral stepwise mechanism. In one study, 51 computational evidence for the existence of a zwitterionic intermediate in the aminolysis of anhydrides has been mentioned, but the zwitterionic intermediate could only be located as a stable minimum on the potential energy surface if a polarizable continuum model for water is considered during the geometry optimization. However, for benzoxazolinones a similar approach did not result in stable zwitterionic geometries 50 and neither for esters nor thioesters have such zwitterionic intermediates been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Free energies of transition states and intermediates were calculated taking 3Ac and hexylamine, optimized separately, as the reference. For conversion from 1 atm standard state to 1 mol L −1 standard state, ΔG values were corrected by subtracting 1.90 kcal mol ‐1 to the calculated value according to an A + B → C reaction as recommended …”
Section: Methodsmentioning
confidence: 99%